Green Synthesis of Silver Nanoparticles Using Soursop Leaf Extract for Photocatalytic Degradation of Textile Wastewater - Iryanti Eka Suprihatin; Ni Made Utami Dwipayanti; Ida Ayu Gede Widihati; Ni Putu Diantariani; Ni Gusti Ayu Dwi Adhi Suastuti; I Gusti Ayu Kunti Sri Panca Dewi; Anak Agung Sagung Alit Sukmaningsih (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This study aimed to synthesize silver nanoparticles (AgNPs) as a photocatalyst and evaluate their performance for textile wastewater photodegradation since previous studies have mainly focused on photocatalytic degradation of model dye compounds, whereas studies using actual textile wastewater remain limited. The synthesis was achieved by extracting soursop leaves and mixing them with AgNO₃ and heating the mixture. After photodegradation reaction condition optimization, the optimum conditions were found at pH of 13, 15 minutes of irradiation time, and a volume of 0.5 mL of AgNPs. Under these conditions, a degradation percentage of 34.37-37.76% was achieved, with a reduction in BOD levels of 5.54-11.08% and COD levels of 8.66-12.22%. These results indicate the potential of AgNPs for textile wastewater treatment, although pretreatment may be required to improve degradation performance. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).